Giving Endorphine Massage Against the Psychological Readiness of Primigravida in Facing Labor - Wahidayanti, Nur; Suwanti, Suwanti (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2022)
Depression stress can be experienced in pregnant women if complaints and causes of change are left. A relatively crucial light massage is given to pregnant women in the time leading up to labor. This study aims to determine the effect of endorphine massage on the psychological readiness of pregnant women primigravida trimester III is facing birth in the working area of Puskesmas. The research design using pre-experiment. The population is the entire pregnant woman primigravida trimester III gestational age 36 weeks. Sampling technique using purpose sampling with a sample count of 30. Data analysis with Wilcoxon. The study results obtained the average level of psychological readiness of pregnant women before being given intervention is 80%. After being given intervention, the psychological readiness level of pregnant in the face of labor is 100%. Statistical tests with Wilcoxon obtained value of p = 0.000 < α = 0.05, there was a significant difference in psychological readiness before and after treatment. There is an effect of endorphine massage on the psychological readiness of pregnant women primigravida trimester III in the face of labor. Endorphine massage can be applied at home with a partner or family to overcome complaints in pregnancy.